Gross Anatomy of Axial Skeleton in Emu (Dromaius novaehollandiae) - Kumar, Pawan; Singh, Gurdial (Indian Journal of Veterinary Anatomy, 2014)
The present study conducted on gross anatomy of axial skeleton of emu highlighted the structural detailsÂ of different bones which can be compared with those of fowl. Emu being flightless bird has several anatomicalÂ differences. The data base may be helpful to anatomists and physiologists to plan future studies and also teachÂ post-graduate students.